Compratative Analysis of Online and Offline Sales of Blacksmith Product Income in the Cibatu Area - Pratiwi, Intan Deanida; Ramadhan, M Fitrah; Algipari, M Fauzan; Rafly, Muhammad Naufal; Ilmi, Salya Aina Zahratani (Neolectura, 2024)
This research aims to analyze the comparison of online and offline sales of blacksmith product income in the Cibatu area. The analytical method used in this journal is a qualitative method by conducting direct interviews with blacksmith sellers in the Cibatu area. The findings from interviews with iron sellers show that on average online sales are more profitable compared to offline income because of advances in technology and the spread of the internet, of course e-commerce is more easily accessible to people throughout the world, which makes online sales increasingly popular. used by local residents to increase income. But offline sales also still have an important role for the local market. However, online sales also affect profit margins due to the resellers involved. ROI on online sales is considered more profitable than offline sales. The results of the analysis highlight the strengths and weaknesses of each sales channel as well as the implications for blacksmith product income in the Cibatu area.